The Productive Citizen: Marx, Cultural Time, and Disability - Pass, Lauren (Stance: an international undergraduate philosophy journal, 2019)
This paper argues for analyzing the systematic invisibility of persons living with disabilities by temporalizing their oppression within a framework of “productive time,” which I posit as a normative sense of time by which cultural products and practices appear within capitalist economies. I argue that productive time is employed in cultural evaluations of actions that render persons with disabilities as “non-productive agents” who cannot partake in historical processes. My hope is that a theory of productive time will assist social justice efforts in analyzing the oppression of particular minority groups by identifying and combating harmful social values.